Degree of esterification and gelling properties of pectin structure in coffee pulp - Rakitikul W. (2017)
© 2016 Trans Tech Publications, Switzerland. Pectin is a high value functional food ingredient widely used as a gelling agent and stabilizer. The chemical structure of pectin has been the subject of scientific investigations for decades. Coffee producers remove beans; the other source of pectin, from coffee cherries is thrown away. Our study showed that pectin extracted from coffee pulp has high degree of esterification and methoxyl content of 93.75% and 7.87 respectively, which indicated good gelation properties. Nevertheless, here we were interested in the primary structure of pectin which is a complex polysaccharides that contains 1, 4-linked α-D-galactosyluronic acid (GalpA) residue. A theoretical dimension, density functional theory (DFT) with Generalized Gradient Approximation (GGA)/BLYP functions, was utilized to study methylester substitution in pectin model compounds. For further discussion, the use of a COSMO model in different solvent showed the significant results in the difference torsion angle and HOMO diagram.